From the editorial to the Book of Portraits on its Way / Iz uvodnika Knjigi portretov na pot - Kranjc, Ivan (Acta Medico-Biotechnica, 2021)
(The book will come out in the publishing house Faculty of Medicine University of Maribor)In 2014, on the tenth anniversary of operations of the University of Maribor Faculty of Medicine, we published the monograph "Ten Years of the Faculty of Medicine of the University of Maribor". In the monograph, we provided a description of the creation and operation of the second Slovenian medical faculty. Much has happened since the first decade and we have already advanced into the second. An attentive observer would not have missed the important milestones of our development from the establishment of the Bologna Reform to our greatest achievement—building an urgently needed faculty on the right riverbank of the Drava River. Following the ideas of the Architecture Professor Boris Podrecca, the faculty is attached to the city and the university. All along, especially since September 2013, we have monitored the development of our medical studies, introduced new features to the program, and developed or renewed basic research studies. Novel appropriate premises and stateof- the-art medical equipment have been the basis for the formation of numerous innovations and changes.